Protective impact of Rosa damascena against neural damage in a rat model of pentylenetetrazole (PTZ)-induced seizure - mansour homayoun; Reyhaneh Shafieyan; Masoumeh seghatoleslam; Seyed Mahmoud Hosseini; Alireza Ebrahimzadeh-bideskan (Mashhad University of Medical Sciences, 2020)
Objective: Based on the previously-declared anticonvulsant properties of Rosa damascena (R. damascena), this study explored the probable effects of R. damascena on neuronal apoptosis in the hippocampus of a rat model of pentylenetetrazole (PTZ)-induced seizure. Materials and Methods: 40 male Wistar rats were randomely divided into control (n=8) and experimental (n=32) groups which underwent PTZ injection. A one-week pre-medication with 50 (PTZ-Ext 50) (n=8), 100 (PTZ-Ext 100) (n=8), and 200 (PTZ-Ext 200) (n=8) mg/kg of hydro-alcoholic extract of R. Damascene was performed while one experimental group (PTZ-induced group) (n=8) received only saline during the week before PTZ injection. After provocation of PTZ-induced seizures, the brains underwent tissue processing and TUNEL staining assay for apoptotic cell quantification. Results: Our findings revealed that PTZ-induced seizures led to apoptosis in neuronal cells of all sub-regions of the hippocampus; yet, only at CA1, CA3 and DG sub-regions of the PTZ-induced group, the difference in the number of apoptotic neuronal cells was significant in comparison with the control group. In addition, pre-medication with the plant extract led to a significant drop in the quantity of apoptotic neurons in these sub-regions in comparison with the PTZ-induced group which received no pre-medication . Conclusion: The results of this study showed that R. damascena extract exerts neuro-protective effects on PTZ-induced seizure.